The Use of N-Smsin (Nurse -Short Message Service Information) Telenursing Application Technology on Compliance With Treatment and Care of Tuberculosis Patients in Preventing Transmission and the Occurrence of Multi Drug Resistant Tuberculosis (International Journal of Scientific Research and Management (IJSRM), 2025)
Tuberculosis is a chronic, infectious disease caused by the bacterium Mycobacterium tuberculosis and remains a global health problem, including in Indonesia. Worldwide, TB is one of the 10 leading causes of death. Poor adherence to treatment is a major obstacle to efficient TB control. Innovative strategies are needed to improve access and adherence to treatment, one of which is the use of the Telenursing N-SMSIn (Nurse-Short Message Service Information) application. The purpose of this study was to determine the effectiveness of the Telenursing N-SMSIn (Nurse-Short Message Service Information) application on adherence to treatment and care for tuberculosis patients, preventing transmission and the occurrence of multidrug-resistant tuberculosis. The research method used a quasi-experimental pretest-posttest with a control group design. The sampling technique used accidental sampling, with a sample of 168 respondents with pulmonary TB in the Woha Community Health Center working area in 2025. The research instrument used the 8-item Morisky Medication Scale. The analysis used the Wilcoxon test and obtained a p-value of 0.001 < 0.05. Therefore, it can be concluded that the implementation of the N-SMSIn telenursing application technology significantly impacts adherence to treatment and care in tuberculosis patients, preventing transmission and the occurrence of multidrug-resistant tuberculosis in the Woha Community Health Center Work Area, Bima Regency.